Value stream mapping key concepts. (LiveLessons (Indianapolis, Ind.), 2022)
4 Hours of Video Instruction Learn value stream mapping key concepts, including the principles of Lean thinking, a high-level overview of the value stream mapping process, and when and how to use this strategic, transformative approach to significantly improve and optimize performance. Overview In this video you learn the key concepts of the value stream mapping process at a high level. Join Donna Knapp, Curriculum Development Manager for ITSM Academy, to learn how to use Lean thinking and techniques to minimize waste and make work flow. Explore the anatomy of a value stream map and the key metrics used to measure flow. Understand also how to create and execute a transformation plan and manage the associated organizational change. Learn How To Learn basic Lean and value stream concepts Explore the elements and anatomy of a value stream map Develop a high level understanding of the value stream mapping process Determine how to identify waste and barriers to flow Discover how to create a transformation plan for the future state of your value stream About the Instructor Donna Knapp has more than 30 years of experience in the IT industry and for more than 15 years has been ITSM Academy's Curriculum Development Manager. Donna teamed with Michael Orzen (coauthor of Lean IT) to develop the Value Stream Mapping Fundamentals certification course. She is a member of the ITIL 4 exam panel and contributed to the ITIL 4 High-velocity IT publication. ITIL 4 reshapes established service management practices in the wider context of value streams, customer experience, digital transformation, and systems thinking. She is a DevOps Institute Ambassador and was the original course author for The DevOps Institute's DevOps Foundation certification course, which is now maintained using feedback from the DevOps community. Donna's years of practical experience and love of learning show in her engaging and informative speaking style and many certifications including the Value Stream Mapping Fundamentals, ITIL® Managing Professional, ITIL® Strategic Leader, and Certified Process Design Engineer certifications, along with numerous DevOps and Site Reliability Engineering (SRE) certifications. She is also a Certified Scrum Master, Certified Agile Service Manager, and Certified Agile Process Owner. Donna is the author of The ITSM Process Design Guide: Developing, Reengineering, and Improving IT Service Management (which serves as the foundation for the Certified Process Design Engineer qualification), as well as two college textbooks, A Guide to Service Desk Concepts, Fourth Edition and A Guide to Customer Service Skills for Service Desk Professionals, Fourth Edition. Donna is a huge fan of W. Edwards Deming and is notorious for evoking his wisdom (#donnasaiddeming). As a citizen of Oldsmar, Florida, Donna also takes great pleasure in the knowledge that the founder of her city, R. E. Olds, is credited with developing the modern assembly line and so was talking about "flow" way before we were all born. Who Should Take This Course IT professionals interested in learning the basics of Lean and value stream mapping, including quality and process improvement professionals, such as process and value stream owners and managers, quality managers, and quality assurance specialists; individuals and teams who want to better understand how to use value stream mapping with a continuous improvement effort such as DevOps or ITSM; line managers, team leaders, and supervisors who want to improve cross-functional collaboration. Course Requirements Some familiarity with modern software engineering, IT operations, and IT service management practices are desirable but not required. Lesson Descriptions Lesson 1: Lean Basic Concepts: In this lesson, we'll explore the five principles of Lean thinking and Lean anti-patterns. As both Lean and value stream mapping are about improving flow, we'll examine ways to make work flow and common barriers to flow. We'll conclude this lesson by comparing value stream mapping to traditional continual improvement techniques and look at situations where they're both appropriate and how they work together. Lesson 2: Value Stream Key Concepts: In this lesson, we'll introduce value stream key concepts. You will learn what a value stream is, how to identify value streams and how value streams integrate with processes. We'll explore the anatomy of a value stream and describe each of its key components. We'll conclude this lesson by describing key value stream metrics and ways to gather and use data when getting started with a value stream mapping initiative. Lesson 3: Value Stream Mapping Key Concepts: In this lesson, we'll introduce value stream mapping key concepts. You'll learn what value stream mapping is and the benefits or the "why" of this technique. We'll introduce value stream mapping roles and deliverables and we'll explore each step in the value stream mapping process. Lessons are devoted to producing current state and target future state value stream maps as well as the transformation plan that's needed to achieve the target future state. We'll conclude this lesson by briefly introducing the emerging value stream management discipline. Lesson 4: Managing the Change: In this lesson, you'll learn what culture is and how value stream mapping and the improvements that flow from it can represent significant culture change for organizations. We'll introduce organizational change management and the components of an organizational change management program. We'll talk about the important role that leadership plays in managing the cultural and organizational change that flows from a value stream mapping initiative and we'll describe the characteristics of a transformational leader. We'll conclude this lesson by describing the characteristics of a learning organization, how to foster a learning culture and the importance of lifelong learning. About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.